2022
DOI: 10.1111/acem.14625
|View full text |Cite
|
Sign up to set email alerts
|

Rising high‐acuity emergency care services independently billed by advanced practice providers, 2013 to 2019

Abstract: Background: Advanced practice providers (APPs) comprise an increasing proportion of the emergency medicine (EM) workforce, particularly in rural geographies. With little known regarding potential expanding practice patterns, we sought to evaluate trends in independent emergency care services billed by APPs from 2013 to 2019. Methods: We performed a repeated cross-sectional analysis of emergency clinicians independently reimbursed for at least 50 evaluation and management (E/M) services (99281-99285, 99291) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…3 We included emergency physicians receiving reimbursement for at least 50 evaluation and management services (99281 to 99285) per year from Medicare part B. 1 , 4 …”
Section: Methodsmentioning
confidence: 99%
“…3 We included emergency physicians receiving reimbursement for at least 50 evaluation and management services (99281 to 99285) per year from Medicare part B. 1 , 4 …”
Section: Methodsmentioning
confidence: 99%
“…Gettel et al 1 showed that APP use has increased since 2013. Other data show that APP use has been increasing for decades.…”
Section: Invited Commentarymentioning
confidence: 99%
“…In this issue of Academic Emergency Medicine, Gettel et al 1 show increasing numbers of U.S. emergency departments (EDs) and high‐acuity visits billed by advanced practice providers (APPs) from 2013 to 2019. The term APP refers to physician assistants (PA) and nurse practitioners (NP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Mr. Wu and Dr. Darracq for their interest in our research regarding the billing of high‐acuity emergency care services by advanced practice providers (APPs) from 2013 to 2019 1 . We agree that descriptive data, such as this, can be used to inform discussions about the changing dynamics of the emergency medical workforce 2,3 …”
mentioning
confidence: 99%